A mão invisível de Júpiter e o método newtoniano de Smith - Cerqueira, Hugo E. A. da Gama (Estudos Econômicos (São Paulo), 2006)
This paper examines Adam Smith's understanding of the philosophy and science, the motivations that lead us to investigate nature and society, and the proper methods of investigation and exposition. The paper also criticizes those authors that interpret Smith's work as an example of the mechanical approach or as a kind of positivism avant la lettre.